Revenue Analysis Of Cattle Farmer In Sub District Patebon Kendal Regency - M. Handayani; Mukson Mukson; R. Yulianingsih (Universitas Wahid Hasyim, 2010)
The purpose of this study to determine conduct of maintenance ofbeef cattle and the influence of production factors to the income breedercattle in Sub district Patebon Kendal Regency. The experiment wasconducted in October 2009 and Location of research taken in the sub districtPatebon Kendal Regency, then selected two villages that have the potentialas a producer of beef cattle. Determination of the location on theconsideration that the District Patebon Kendal District is an area of lowlandtropical climates have great potential in the development of beef cattlefattening. The research method used is survey method. The amount ofsamples was 60 respondents from the two villages, each village was taken30 samples. Methods of data analysis using multiple linear regressionanalysis. The results showed simultaneous production factors affect revenuecattle farmer, the significance value of 0.003 (p <0.01). Partially laboreffusion is very influential on revenue of cattle farmer with a significancevalue of 0.000 (p <0.01), while the cost of feed grasses, feed concentratecosts and the number of livestock has no effect on the income of cattle, thesignificance values obtained at 0.341; 0.334 and 0.705 (p> 0.05).Mathematical model is Y = 457,820.5 + 0.88 X1 - 0.443 X2 + X3 +27077.239 X4 110,609.0Keywords : income farmer, beef cattle